ORGANIZATIONAL-ECONOMIC BASES OF MANAGEMENT OF CURRENT COSTS ON PROCESSING ENTERPRISES OF SPIRIT PRODUCTION (ON THE EXAMPLE MARIINSKY JSC “ALCOHOL FACTORY”) - Ryabko T.V.; Dyoro A.A. (Техника и технология пищевых производств)
The effectiveness of the company depends on a number of criteria such as: the correct management strategy, the competitiveness of products, including the management costs level, flexible enterprise management system that presupposes regulating, purposeful influence on the process of "input-output". In modern conditions it is important to use effective cost management methods for agricultural enterprises. In the cost structure, ongoing costs occupy the major share. This study examines the features of the current cost management in the agribusiness companies, identifying existing gaps and identify mechanisms to rectify these shortcomings. Methodology of management of current costs, enclosed in the application of the system of marginal revenue and ongoing cost control mechanism for the processing of agricultural enterprises is largely determined by the centers of responsibility as a source of rapid response cost management system. As a result of the application of this method was found unprofitable production of raw spirit in the analyzed company, while the production of alcohol of the highest purification and "luxury" product has a positive financial result. Measures that aimed at reducing costs in the production process and improve the efficiency of production and economic activity of JSC "Alcohol Factory", the main of which is the interaction with agricultural producers with a view to identifying reserves to reduce the acquisition costs of raw materials (grain), thereby reducing the cost of production were presented.